2010
DOI: 10.1007/s10495-010-0554-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ROS/MAPK signaling pathways by okadaic acid leads to cell death via, mitochondrial mediated caspase-dependent mechanism

Abstract: Okadaic acid (OA) is a specific and potent protein phosphatase inhibitor and tumor promoter. The present study establishes the role of reactive oxygen species (ROS) and mitogen activated protein kinases in cell death induced by okadaic acid. The study showed that okadaic acid is cytotoxic at 10 nM with an IC50 of 100 nM in U-937 cells. The CVDE assay and mitochondrial dehydrogenase assay showed a time dependent cytotoxicity. The phase contrast visualization of the OA treated cells showed the apoptotic morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 56 publications
(61 reference statements)
9
72
0
Order By: Relevance
“…32 Mitochondrial dysfunction activates caspases and promotes apoptosis. 53 Here, we have shown that HEP-Flury and particularly GD-SH-01 activate apoptosis and provoke a decrease of the MMP simultaneously. Autophagy as well as apoptosis constitutes 2 intracellular processes through which superfluous, damaged or aged cells or organelles are eliminated and several reports have provided evidence for a connection between these 2 pathways.…”
Section: Discussionmentioning
confidence: 64%
“…32 Mitochondrial dysfunction activates caspases and promotes apoptosis. 53 Here, we have shown that HEP-Flury and particularly GD-SH-01 activate apoptosis and provoke a decrease of the MMP simultaneously. Autophagy as well as apoptosis constitutes 2 intracellular processes through which superfluous, damaged or aged cells or organelles are eliminated and several reports have provided evidence for a connection between these 2 pathways.…”
Section: Discussionmentioning
confidence: 64%
“…Mitochondria-generated ROS plays a potent role in the release of cytochrome c and other pro-apoptotic proteins, which can trigger caspase activation and apoptosis [21,37]. When the formation of ROS is enhanced, it can still influence the viability of cells and impair mitochondrial function, such as respiration and oxidative phosphorylation, mitochondrial permeability transition (MPT) and MMP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-defined role of mitochondria in energy metabolism, regulation of cell apoptosis has recently emerged as second major function of these organelles [17][18][19][20][21][22]. Mitochondrion has an important role in caspase-dependant and caspase-independent pathways of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…33 Additionally, p38 MAPK is pivotal in the apoptosis induced by chemotherapy drugs. [34][35][36] In recent studies, the activation of p38 MAPK has been suggested to be induced by Aurora B kinase inhibition. 37,38 However, the role of p38 MAPK in VX680-induced effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%